Implementação do Consultório na Rua em um município do interior de São Paulo - Pereira, Caroline dos Santos (2021)
This dissertation aims to analyze the process of implementing the Street Clinic in a city in the interior of São Paulo. This is a descriptive-exploratory study with a qualitative approach. Five respondents participated in the study, with the inclusion criterion working or having worked providing services directly or indirectly to the homeless population by the Municipal Department of Citizenship and Social Assistance or Municipal Health Department. Professional exclusion criteria under the age of 4 years at the Municipal Secretariat of Citizenship and Social Assistance or Municipal Health Secretariat. The municipality has a Consultancy team on street of modality 1, implemented in 2017. Semi-structured interviews were carried out by Google Meet with professionals from the Citizenship and Assistance Secretariat Social and Health for data collection. As a result, two categories emerged: Street Clinic: condition of eternal constrution and Challenges of the intrasectoral and intersectoral network. We concluded that the Street Clinic in the municipality of the study represents an advance in the health issues of people living on the streets, the difficulties of access, prejudices and attempts to articulate with the intra and intersectoral network.